LncRNA LYPLAL1-DT screening from type 2 diabetes with macrovascular complication contributes protective effects on human umbilical vein endothelial cells via regulating the miR-204-5p/SIRT1 axis - Xiao Zhu; Yihan Liu; Jia Cui; Jianyi Lv; Changlong Li; Jing Lu; Xueyun Huo; Jingtao Dou; Zhigang Bai; Zhenwen Chen; Xiaoyan Du (Cell Death Discovery, 2022)
Abstract Long noncoding RNAs (lncRNAs) are involved in diabetes related diseases. However, the role of lncRNAs in the pathogenesis of type 2 diabetes with macrovascular complication (DMC) has seldomly been recognized. This study screened lncRNA profiles of leukocytes from DMC patients and explored protective role of lncRNA LYPLAL1-DT in endothelial cells (EC) under high glucose (HG) and inflammatory conditions (IS). Between DMC and healthy controls, 477 differential expression lncRNAs (DE-lncRNAs) were identified. The enrichment and pathway analysis showed that most of the DE-lncRNAs belonged to inflammatory, metabolic, and vascular diseases. A total of 12 lncRNAs was validated as significant DE-lncRNAs in expanding cohorts. Furthermore, these DE-lncRNAs were shown to be significantly related to hypoxia, HG, and IS in EC, especially lncRNA LYPLAL1-DT. LYPLAL1-DT overexpression results in the promotion of the proliferation, and migration of EC, as well as an elevation of autophagy. Overexpressed LYPLAL1-DT reduces the adhesion of monocytes to EC, boosts anti-inflammation, and suppresses inflammatory molecules secreted in the medium. Mechanistically, LYPLAL1-DT acts as competing endogenous RNA (ceRNA) by downregulating miR-204-5p, therefore enhancing SIRT1 and protecting EC autophagy function; thus, alleviating apoptosis. Finally, exosome sequencing revealed LYPLAL1-DT expression was 4 times lower in DMC cells than in healthy samples. In general, we identified LYPLAL1-DT having protective effects on EC as ceRNA mediated through the miR-204-5p/SIRT1 pathway. Therefore, it inhibits the autophagy of EC as well as modulating systemic inflammation. This approach could be regarded as a new potential therapeutic target in DMC.